2016
DOI: 10.4172/2157-7609.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Retinal Structure and Function of Mother Wistar Rats Supplemented Aspartame, Glutamate and Galactose

Abstract: Three dietary supplements are investigated in the present study. Aspartame is a low calorie sweetener utilized instead of sugar for diabetic patients. Monosodium Glutamate (MSG) is used in varieties of food stuffs to enhance food flavor. Meanwhile galactose is presents in many of food items such as milk, dairy products, fruits and vegetables and overloads enhanced aging like process and altered body function. The present work aimed to illustrate the effect of dietary supplements of aspartame, glutamate and gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It has also been reported to lead to degeneration of neurons in retinal layers, the arcuate nucleus, and various other brain regions, delaying the emergence of certain reflexes during neurobehavioral development and leading to temporary changes in reflex performance and motor coordination [ 59 , 60 ]. El-Sayyad et al [ 61 ] found that MSG given orally to pregnant rats significantly reduced total retinal thickness, outer and inner nuclear layers, and photoreceptor layer thickness. It has also been reported that mother rats have retinal ganglion degeneration, loss of pigment epithelium, and vacuolization in the plexiform inner layer.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported to lead to degeneration of neurons in retinal layers, the arcuate nucleus, and various other brain regions, delaying the emergence of certain reflexes during neurobehavioral development and leading to temporary changes in reflex performance and motor coordination [ 59 , 60 ]. El-Sayyad et al [ 61 ] found that MSG given orally to pregnant rats significantly reduced total retinal thickness, outer and inner nuclear layers, and photoreceptor layer thickness. It has also been reported that mother rats have retinal ganglion degeneration, loss of pigment epithelium, and vacuolization in the plexiform inner layer.…”
Section: Introductionmentioning
confidence: 99%